Evaluation of Maize (Zea mays L.) Genotypes for Salt Tolerance - Khorasani, Saeed Khavari; Khazaee, Hadi; Mohammadi, Mohammad (Asian Journal of Biological and Life Sciences, 2017)
The current study was carried out to screen 45 different maize (Zea mays L.) genotypes (23 inbred lines and 22 hybrids) against salt tolerance by evaluating germination percentage, vigor index and growth as well as yield and yield components. The greenhouse and filed experiments were conducted in Mashhad, Iran in 2009, using completely randomized design (CRD) and complete randomized block design (RCBD), respectively. Different salinity levels (1, 4, 8 and 12 dsm-1) were used in the greenhouse experiments, whereas field experiment was conducted on a saline soil (5.9 -1 dsm ). In both experiments, irrigation was performed using saline water too. Days to anthesis, days to silking, anthesis-silking interval (ASI), days to physiological maturity, plant height, ear height, leaves number per plant, leaves number above ear, yield components and yield were measured from the field experiment. Germinating was deferred by 8 and 12 dsm salinity levels, however the seedlings of all genotypes remained alive up to 12 dsm-1 salinity level. Plant height, ear height, days to anthesis, yield and yield components affected by salinity at the field experiment. Results showed that maize hybrids were more tolerated to salinity compared with inbred lines. Among the hybrids, the highest yields were produced by KE72012/1-12 × -1 K2331(7.772 ton/ha), KSC500 and ZP434, respectively. The lowest grain yield (2.89 ton ha-1) was obtained from hybrid ETH-M82. The highest (1.72 ton ha-1) and lowest (0.279 ton ha-1) grain yield in inbred lines was produced by KE72012/1-12 and OH43/1-42, respectively.
Keywords: Anthesis; Plant height; Silking; Yield components